2018
DOI: 10.7717/peerj.5915
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of asexual recruitment of Pocillopora acuta in Okinawa Island using genotypic identification

Abstract: Okinawa Island is located near the center of the Nansei Islands (∼24–31°N), at a relatively high latitude for coral reefs. Nevertheless, more than 80 coral genera (over 400 species) are abundant in the Nansei Islands. Since March, 2017, scleractinian corals have been held in an outdoor tank at the OIST Marine Science Station at Seragaki, Onna with natural sea water flow-through in order to be used in molecular biological and physiological studies. In January, 2018, we found small pocilloporid-like colonies sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Our results suggest that the diploid P. acuta are both sexual outbreeders and generate asexual brooded larvae, as previously described (Nakajima et al 2018; Richmond and Jokiel 1984; Schmidt-Roach et al 2014). The evolution of triploid genotypes in this species may be an adaptation to local conditions in Kāne‘ohe Bay, possibly allowing them to outcompete the ancestral diploid genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…Our results suggest that the diploid P. acuta are both sexual outbreeders and generate asexual brooded larvae, as previously described (Nakajima et al 2018; Richmond and Jokiel 1984; Schmidt-Roach et al 2014). The evolution of triploid genotypes in this species may be an adaptation to local conditions in Kāne‘ohe Bay, possibly allowing them to outcompete the ancestral diploid genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…P. acuta is a brooding species, which implies limited dispersal of larvae before settlement, compared to a broadcast spawning species (Torda et al 2013a). In addition, P. acuta exhibits both sexual and asexual reproductive modes (Torda et al 2013a;Schmidt-Roach et al 2014b;Ge ´lin et al 2017;Nakajima et al 2018). Whilst populations in the Palm Island archipelago preferentially use sexual reproduction, particular sites within the Palm Islands received a greater proportion of recruits than others when examined over a period of two years (Torda et al 2013a).…”
Section: Near-complete Lack Of Endozoicomonas Regardless Of Bleaching Severitymentioning
confidence: 99%
“…For instance, it is welldocumented that different coral colonies of a given species, exposed to similar levels of thermal stress at the same location can exhibit varying degrees of bleaching (Swain et al 2016;Green et al 2019); however, we do not know if this mosaic of bleaching phenotypes observed at the colony-level is reflected in the microbiome. To address this question, we used the emerging model species Pocillopora acuta, a reef-building coral with well characterised ecology, reproduction and microbiome (Torda et al 2013a;Schmidt-Roach et al 2014a, b;Nakajima et al 2018;Damjanovic et al 2020b;Ros et al 2021). Previous studies have revealed that the microbiomes of Pocillopora species are generally stable under changing environmental conditions (Pogoreutz et al 2018;Epstein et al 2019), with species such as P. acuta often hosting site-specific microbiomes (Torres et al 2020), perhaps due to the brooding reproductive strategy of the host (Torda et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, P. verrucosa has been found to brood in nearby Philippines (Villanueva et al., 2008) that wintertime P. verrucosa recruits could actually be brooded; however, further study is required. Several other pocilloporids can reproduce asexually, which could provide an alternative explanation for winter recruitment: Pocillopora acuta may generate planula asexually in the absence of sperm (Nakajima et al., 2018; Smith et al., 2019), and P . damicornis may produce clonal larvae, although this behavior may vary along latitudinal gradients (Miller & Ayre, 2004).…”
Section: Discussionmentioning
confidence: 99%